2010
DOI: 10.1002/fuce.200900038
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Supported CoSe2 Nanoparticles for Oxygen Reduction Reaction in Acid Medium

Abstract: Carbon‐supported CoSe2 nanoparticles, as non‐precious metal cathodic catalyst, were prepared via the in situ surfactant‐free method with the conventional heating. Structural and electrochemical properties of the obtained 20 wt.‐% CoSe2/C nanoparticles were investigated by means of powder X‐ray diffraction (PXRD), differential thermal gravimetric analysis (DTA‐DTG) and rotating disc electrode (RDE) techniques. CoSe2 nanoparticles have two kinds of crystal structure after heat treatment under nitrogen at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 40 publications
2
84
0
Order By: Relevance
“…Among them, cobalt based selenides (CoSex) are attracting enormous interest as new ORR electrocatalysts. For example, CoSe2/C obtained by Feng et al [5,6] showed superior electrocatalytic activity towards ORR with an open circuitry potential of 0.81 V in 0.5 M H2SO4, and higher methanol tolerance than that of Pt/C. Susac et al [7] exhibited that cobalt-selenium (Co-Se) with varying content of Se obtained by magnetron sputtering and chemical methods indicated a electrocatalytic activity towards ORR in an acidic electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cobalt based selenides (CoSex) are attracting enormous interest as new ORR electrocatalysts. For example, CoSe2/C obtained by Feng et al [5,6] showed superior electrocatalytic activity towards ORR with an open circuitry potential of 0.81 V in 0.5 M H2SO4, and higher methanol tolerance than that of Pt/C. Susac et al [7] exhibited that cobalt-selenium (Co-Se) with varying content of Se obtained by magnetron sputtering and chemical methods indicated a electrocatalytic activity towards ORR in an acidic electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the ORR activity on the Co-Se system, the methanol tolerance was further investigated in alkaline medium [102]. Without surprise, the CoSe2 nanocatalyst performance in alkaline medium is better than that in acid medium revealing further that the carbon-supported cubic phase of CoSe2 is a promising non-precious electrocatalyst for alkaline fuel cells [103]. Furthermore, the oxygen reduction activity of 20 wt % CoSe2/C in 0.1 M KOH was slightly higher than that of Co3O4/rmGO (reduced mildly oxidized graphene oxide) and comparable to that of Co3O4/NrmGO (nitrogen-doped mildly oxidized graphene oxide) as reported by Liang et al [104].…”
Section: Non-precious Catalystsmentioning
confidence: 99%
“…Recently, non-precious metal chalcogenides, e.g., MS2 {M = Fe [9], Co and (Co, Ni) [10]} thin film, CoS2 [11], CoSe2 [12,13], Co1−xS [14] nanoparticles have attracted extensive attention due to promising catalytic activity for ORR, low cost and abundant reserve in the earth's crust. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [13,14], one notes that heat treatment plays an important role to produce electrocatalysts with high performance. However, Dai and his coauthors did not explain the reason for annealing treatment in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation